The Implementation of Formative Assessment in Social Science Learning for Grade V at SD Negeri 25 Pagar Alam - Evriani, Nova Tri; Rahmani, Rahmani (TOFEDU: The Future of Education Journal, 2025)
The learning process that is less participatory and interactive also becomes an important factor. Students feel less involved in the learning process, which hinders their understanding and retention of the material. The lack of interaction between students and teachers, as well as among students themselves, impacts low motivation and enthusiasm for learning. This phenomenon needs to be addressed seriously in order to improve the quality of education and achieve optimal learning outcomes. Therefore, effective strategies and solutions are required to overcome understanding gaps, increase student participation, and optimize the learning process. The data collection technique in this study was conducted through triangulation. This research is a qualitative descriptive study with inductive data analysis. The results of qualitative research focus more on understanding meanings than on efforts to generalize. The implementation of Formative Assessment in the Social Science learning process for Grade V at SD Negeri 25 Pagar Alam has been carried out systematically and in accordance with assessment principles that are process-oriented. The implementation of Formative Assessment in the Social Science learning process.